CLINOHOLMQUISTITE DISCREDITED: THE NEW AMPHIBOLE END-MEMBER FLUORO-SODIC-PEDRIZITE - Oberti R.; Cámara F.; Ottolini L. (My University, 2005)
Re-examination of holotype “clinoholmquistite”, ideally A□BLi2 C(Mg3Al2) TSi8 O22 X(OH)2 (Ginzburg 1965) from the Tastyg spodumene deposit, Tuva, Siberia, Russia by EMP and SIMS analysis and structure refinement shows that the sample consists of a mixture of two distinct amphibole compositions, tremolite and a new amphibole end-member, fluoro-sodic-pedrizite, ideally ANa BLi2 C(Mg2Al2Li) TSi8 O22 XF2 (IMA-CNMMN 2004-002). Fluoro-sodic-pedrizite from Tastyg has the following crystal-chemical formula and unit-cell parameters: A(Na0.64K0.01) B (Li1.93Ca0.04Na0.03) M1 (Mg1.69Fe2+0.31) M2 (Al1.98Cr0.01Zn0.01) M3 (Li0.64Fe2+0.21Mg0.13Mn0.02) T1 (Si3.96Al0.04) T2 Si4 O22 X (F1.10OH0.90), a = 9.368(8), b = 17.616(10), and c = 5.271(4) Å, β = 102.38(4)°, V = 849.6 Å3, Z = 2. The structure has been refined to Robs = 2.3% (I > 3σI) and Rall = 3.8%. Refined site-scattering values and site-geometries were used, together with EMP and SIMS results, to obtain site populations. Fluoro-sodic-pedrizite is the first amphibole end-member with dominant CLi found in Fe-poor geologic environments. The coexisting tremolite contains only 0.002 wt% Li2O and 0.06 wt% B2O3, probably ordered at the T1 site. Crystal-chemical arguments, as well as preliminary experimental work, suggest clinoholmquistite is unstable.
Keywords: clinoholmquistite; amphibole